House price responses to monetary policy surprises: Evidence from the U.S. listings data - Denis Gorea; Oleksiy Kryvtsov; Marianna Kudlyak (Bank of Canada, 2022)
Existing literature documents that house prices respond to monetary policy surprises with a significant delay, taking years to reach their peak response. We present new evidence of a much faster response. We exploit information contained in listings for residential properties for sale in the United States between 2001 and 2019 from the CoreLogic Multiple Listing Service Dataset. Using high-frequency measures of monetary policy shocks, we document that a one- standard-deviation contractionary monetary policy surprise lowers housing list prices by 0.2%- 0.3% within two weeks-a magnitude on par with the effect on stock prices. House prices respond more strongly to the surprises to future rates as compared with the surprise changes in the federal funds rate. Sale prices are mostly predetermined by list prices and do not respond independently to monetary policy surprises.
Keywords: E52; R21; R31; 330; Housing; Inflation and prices; Interest rates; Monetary policy transmission